Applying Abatement Cost Curve Methodology for Low-Carbon Strategy in Changning District, Shanghai - World Bank (Washington, DC, 2014)
The speed and scale of urbanization provide an unprecedented opportunity in the coming years to invest in clean energy technologies to contain carbon emissions from the country's sprawling cities. Therefore, supporting low carbon cities is one of the government's top priorities. Shanghai municipal and changning district governments are firmly committed to the transition to a low-carbon city and requested for the World Bank's support in making changning district and Shanghai leaders in designing novel and efficient ways to achieve carbon-intensity-reduction targets. This report documents the methodology of and key findings from applying abatement cost curves and scenarios to set low-carbon targets and define cost-effective low-carbon investment programs in Changning district, Shanghai. At the request of changning district government, the Bank team supported a Shanghai energy conservation institution, assisted by an international firm, in conducting a comprehensive survey of buildings in Hongqiao area in the changning district, and in developing carbon dioxide (CO2) abatement cost curves to identify the abatement potential, cost, and ease of implementation of various mitigation measures. Three alternative abatement scenarios were developed to establish an ambitious low-carbon target for Hongqiao area. The use of CO2 abatement cost curves, bottom-up investigation surveys, and ease-of-implementation considerations for defining an investment program to reduce CO2 emissions were the first of its kind at the time. The abatement cost curve developed under this upstream analytical work allowed the district government to make informed decisions about medium-term targets for CO2 abatement and to identify priority actions and investments to meet them. This study also provides the solid analytical underpinning for the design of the World Bank and Global Environment Facility (GEF) green energy for low-carbon city in Shanghai project. It includes the following chapters: executive summary; the objectives: 12th five-year plan carbon intensity reduction target and beyond; the methodology: a bottom-up and comprehensive approach; the bottom-up survey: data collection and identification of abatement technologies; the abatement measures: carbon abatement cost curves; the abatement priorities: abatement technologies ranked by cost and ease of implementation; the low-carbon targets: abatement scenarios for 2015 and 2020; from abatement cost curve to implementation: green energy for low-carbon city in Shanghai project; and the significance: potential replications in other cities.